PERKARA, PUTUSAN, DAN PEMULIHAN - Rully Simorangkir; Yohanes Parapat; Stenly Reinal Paparang (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2026)
This article maintains that John 8:3–11 can be read not only as a story of mercy, but also as an adjudicative account in which Jesus takes a judicial role. Although many interpretations rightly give attention to Jesus' compassion and to his offer of life for the woman brought before him, this study argues that the offer comes through judgment rather than apart from it. The article, using qualitative library research and a narrative-juridical approach, examines the pericope as a case set before an authoritative figure and followed through accusation, norm, response, and final disposition. Jesus, in this reading, receives the case, examines it by exposing the accusers' moral and procedural failure, delivers a verdict that redirects the whole matter, and resolves it through a final statement that gives status and makes moral transformation possible. John 8:3–11, therefore, is better seen not as the lack of judgment, but as restorative judgment in which mercy becomes the manner of a just decision.